[PP.03.08] THE HAEMODYNAMIC MECHANISM OF THE AGE-RELATED INCREASE IN PULSE PRESSURE IN WOMEN. (September 2017) - Li, Y.; Jiang, B.; Keehn, L.; Cecelja, M.; Spector, T.; Chowienczyk, P.
Abstract : Objective: An age-related increase in pulse pressure is the major cause of morbidity and mortality in the ageing population and is more marked in women than in men. The haemodynamic determinants of increased pulse pressure remain incompletely understood. The aim of this study is was to examine the contribution of ventricular dynamics, large artery stiffness, and pressure wave reflection to central pulse pressure. Design and method: A total of 2162 women aged 18 to 91 years (mean ± SD, age 57 ± 13 years) from the Twins UK cohort were studied. Non-invasive aortic flow velocity and blood pressure were measured by Doppler sonography and carotid tonometry system respectively. Carotid-femoral PWV was measured using the SphygmoCor system. Reflection index (the ratio of the peak of the backward pressure wave over that of the forward pressure wave) was computed from the pressure and flow waves. Results: Central pulse pressure increased with age, from 29.5 ± 0.46 mmHg for those aged below 40 years to 52.6 ± 0.85 mmHg for those over 70 years (means ± SE, P < 0.001). PWV increased approximately 13.2% per decade. Maximum flow velocity tended to increase (from 1.11 ± 0.01 to 1.16 ± 0.01 m/s over the 5 decades, P < 0.01), and ejection volume at the time of peak pulse pressure increased from 63.3 ± 1.41 to 72.3 ± 1.92 ml (P < 0.001) but reflection index decreased from 0.28 ± 0.01 to 0.25 ± 0.01 (P < 0.001). Conclusions: These results suggest that the age-related increase in central pulse pressure is driven mainly by an increase in arterial stiffening and increased ventricular ejection.